Experimental Long-Term Effects of Early-Childhood and School-Age Exposure to a Conditional Cash Transfer Program - Teresa Molina Millán; Karen Macours; John Maluccio; Luis Tejerina (Institute of Labor Economics (IZA), 2019)
Numerous evaluations of conditional cash transfer (CCT) programs show positive short-term impacts, but there is only limited evidence on whether these benefits translate into sustained longer-term gains. This paper uses the municipal-level randomized assignment of a CCT program implemented for five years in Honduras to estimate long-term effects 13 years after the program began. We estimate intent-to-treat effects using individual-level data from the population census, which allows assignment of individuals to their municipality of birth, thereby circumventing migration selection concerns. For the non-indigenous, we find positive and robust impacts on educational outcomes for cohorts of a very wide age range. These include increases of more than 50 percent for secondary school completion rates and the probability of reaching university studies for those exposed at school-going ages. They also include substantive gains for grades attained and current enrollment for others exposed during early childhood, raising the possibility of further gains going forward. Educational gains are, however, more limited for the indigenous. Finally, exposure to the CCT increased the probability of international migration for young men, from 3 to 7 percentage points, also stronger for the non-indigenous. Both early childhood exposure to the nutrition and health components of the CCT as well as exposure during school-going ages to the educational components led to sustained increases in human capital.
Keywords: I25; I28; I38; O15; 330; conditional cash transfers (CCTs); early childhood; education; migration